OVERVIEW OF THE DEVELOPMENT OF WORLD RELIGIONS AND THE HISTORY OF THEIR SPREAD IN THE NUSANTARA - Yogi Prihantoro; Peni Nurdiana Hestiningrum (QUAERENS: Journal of Theology and Christianity Studies, 2020)
Whether the entry of world religions into Indonesia is driven more by puritanical economic, political, or missiological (da'wah) motives, has colored the uniqueness of each, and has influenced the thickness or thinness of tolerance levels towards the presence of "the other." How to read economic, political, or missiological relations in these relations which are not as simple as imagined. So the article has the aim of understanding how the development of world religions and the history of their development in the archipelago at a glance. The method used is an evaluative literature study, where each discussion of religions ends with an evaluation of their development. Masuknya agama-agama dunia ke Indonesia pakah itu lebih didorong motif ekonomis, politik, atau motif misiologis (da’wah) yang lebih puritan, telah mewarnai kekhasan masing-masing, dan mempengaruhi tebal atau tipis tingkat toleransi terhadap kehadiran “yang lain” (the others). Bagaimana membaca relasi ekonomi, politis atau misiologis dalam relasi ini yang ternyata tidak sesederhana seperti dibayangkan. Maka artikel memiliki tujuan memahami bagaimana perkembangan agama-agama dunia dan sejarah perkembangannya di Nusantara secara selayang pandang. Metode yang digunakan adalah studi literatur evalutif, dimana setiap pembahasan agama-agama diakhiri dengan evaluasi dari perkembangannya.